Mobile Application of Food Recommendation for Allergy Baby Using Rule-Based Technique - Shari A.A.; Pajar N.A.; Sabri N.; Mohd Noordin M.R.; Ishak Zainudin F.M.; Shari A.S.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus